2013
DOI: 10.1371/journal.pone.0063964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enhanced Attention to Local Detail in Anorexia Nervosa Using the Embedded Figures Test; an fMRI Study

Abstract: The behavioural literature in anorexia nervosa and autism spectrum disorders has indicated an overlap in cognitive profiles. One such domain is the enhancement of local processing over global processing. While functional imaging studies of autism spectrum disorder have revealed differential neural patterns compared to controls in response to tests of local versus global processing, no studies have explored such effects in anorexia nervosa. This study uses functional magnetic resonance imaging in conjunction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 53 publications
4
34
2
Order By: Relevance
“…As such, the paradigm requires participants to switch their attention between two stimuli to search for the simple shape and utilize a more global strategy to successfully perform the task. Our previous cross-sectional fMRI findings on the EFT reported poorer performance in AN alongside greater task-related activation in the fusiform gyrus and greater task-related deactivation in the posterior cingulate cortex [19]. Their poorer performance was in line with previous literature on central coherence [6,7], and the changes in BOLD response suggested that those with AN do not direct their neural effort as efficiently as controls.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As such, the paradigm requires participants to switch their attention between two stimuli to search for the simple shape and utilize a more global strategy to successfully perform the task. Our previous cross-sectional fMRI findings on the EFT reported poorer performance in AN alongside greater task-related activation in the fusiform gyrus and greater task-related deactivation in the posterior cingulate cortex [19]. Their poorer performance was in line with previous literature on central coherence [6,7], and the changes in BOLD response suggested that those with AN do not direct their neural effort as efficiently as controls.…”
Section: Discussionsupporting
confidence: 87%
“…On the Embedded Figures Tests (described in detail in [19]), the participants were required to indicate which of two figures contained a simple geometrical shape by moving a joystick to the left or to the right. The level of difficulty varied, and the figures were either simple (SEF) or complex (CEF) in composition (see [25] for further details).…”
Section: Paradigmsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 These abnormalities are thought to rely on alterations of long-range connections between prefrontal and parieto-occipital areas in other disorders, 45 and these same areas also seem to be implicated in weak central coherence in patients with anorexia nervosa. 46 However, the specific role of the SLF in these deficits in patients with anorexia nervosa remains to be further investigated.…”
Section: J Psychiatry Neurosci 2014;39(6)mentioning
confidence: 99%